The Role of Mitochondria in Aging and Modern Anti-Aging Therapeutic Approaches - Teguh Tanuwidjaja (Jurnal EduHealth, 2025)
Aging is a complex biological process characterized by a progressive decline in cellular and tissue function, ultimately affecting homeostasis and the overall health of the organism. One of the main mechanisms involved in the aging process is mitochondrial dysfunction, the energy-producing organelles that also play a crucial role in regulating oxidative stress, apoptosis, and cellular metabolism. This study aims to analyze the role of mitochondria in the aging mechanism and review various modern anti-aging therapeutic approaches that focus on restoring mitochondrial function. The research method used was a literature review, reviewing the latest scientific literature on mitochondrial biology, cellular aging processes, and potential therapies such as the use of mitochondrial antioxidants. The results indicate that mitochondria play a crucial role in the aging process through oxidative stress and mitochondrial DNA (mtDNA) damage, which leads to decreased energy production and cellular dysfunction. When the number of free radicals increases and mitochondrial repair capacity decreases, cells become vulnerable to damage that triggers aging and degenerative diseases such as Alzheimer's and Parkinson's. Various modern therapeutic efforts have been shown to improve this condition, including the use of mitochondria-targeted antioxidants (MitoQ), mitochondrial biogenesis-stimulating compounds (methylene blue), and SIRT1 activation to enhance cell defense. Lifestyle approaches such as regular exercise and a healthy diet also support mitochondrial function, while mitochondrial transplantation in animal studies has shown promising results in improving energy and slowing aging.